Semblance of the life and work of Dr. Antonio Trinidad Santos. - Espinosa Victoria, David; Rentería Chávez, Ma. Concepción (REVISTA TERRA LATINOAMERICANA, 2018)
Dr. Antonio Trinidad Santos can be defined as an enthusiastic researcher of Andosols and their agricultural productivity. Probably, corn, amaranth and litchi were the crops to which he devoted most of his scientific life. With the present semblance, the Mexican Soil Science Society A.C. recognizes post mortem one of its most distinguished members and the legacy he left to future soil scientists.